Responses to the Hydrostatic Pressure of Surface and Subsurface Strains of Pseudothermotoga elfii Revealing the Piezophilic Nature of the Strain Originating From an Oil-Producing Well - Roumagnac, Marie; Pradel, Nathalie; Bartoli, Manon; Garel, Marc; Jones, Aaron A.; Armougom, Fabrice; Fenouil, Romain; Tamburini, Christian; Ollivier, Bernard; Summers, Zarath M.; Dolla, Alain (Frontiers in Microbiology, 2020)
Microorganisms living in deep-oil reservoirs face extreme conditions of elevated temperature and hydrostatic pressure. Within these microbial communities, members of the order Thermotogales are predominant. Among them, the genus Pseudothermotoga is widespread in oilfield-produced waters. The growth and cell phenotypes under hydrostatic pressures ranging from 0.1 to 50 MPa of two strains from the same species originating from subsurface, Pseudothermotoga elfii DSM9442 isolated from a deep African oil-producing well, and surface, Pseudothermotoga elfii subsp. lettingae isolated from a thermophilic sulfate-reducing bioreactor, environments are reported for the first time. The data support evidence for the piezophilic nature of P. elfii DSM9442, with an optimal hydrostatic pressure for growth of 20 MPa and an upper limit of 40 MPa, and the piezotolerance of P. elfii subsp. Lettingae with growth occurring up to 20 MPa only. Under the experimental conditions, both strains produce mostly acetate and propionate as volatile fatty acids with slight variations with respect of the hydrostatic pressure for P. elfii DSM9442. The data show that the metabolism of P. elfii DSM9442 is optimized when grown at 20 MPa, in agreement with its piezophilic nature. Both Pseudothermotoga strains form chained cells when the hydrostatic pressure increases, especially P. elfii DSM9442 for which 44 % of cells are chained when grown at 40 MPa. The viability of the chained cells increases with the increase in the hydrostatic pressure, indicating that chain formation is a protective mechanism for P. elfii DSM9442.